Lipid disorders in transitional societies with particular reference to triglycerides and HDL-cholesterol - Vichai Tanphaichitr (2018)
Like Western populations, affluent urban populations in developing countries are facing the problem of dyslipidemia, an important risk factor of coronary heart disease. Our study of 453 affluent, urban Thai women revealed that the prevalences of type IIa, IIb, IV and V hyperlipoproteinemias were 32.5, 2.2, 2.4, and 0.4%, respectively. Based on a waist-over-hip circumference ratio (WHR) of > 0.8 and body mass index (BMI) of > 25.0 kg/m2 to indicate abdominal and overall obesity, respectively, the prevalences of abdominal obesity, overall obesity, and combined abdominal and overall obesity in these women were 32.9, 5.7, and 21.2%, respectively. Both BMI and WHR in these women had significantly positive influences on their serum triglyceride (TG) and apo B levels, and significantly negative influences on their serum HDL-cholesterol levels. Only BMI had a significantly positive influence on their serum total cholesterol (TC) and LDL-cholesterol levels but a significantly negative influence on their serum apo A-I levels. A lipid-lowering effect of linoleic acid was shown in 101 dyslipidemic women receiving dietary intervention for 8 weeks, evidenced by significantly negative relationships between their serum 18:2 n-6 levels and serum TC, LDL-C, TG, and apo B levels.